Dorsal and Pelvic Fin Deformities in Egirdira nigra (Teleostei, Leuciscidae), an Endangered and Endemic Species Collected from Eğirdir Lake, Türkiye - Jawad , L. A.; Güçlü, S. S.; Küçük, F.; Yıldırım , U. G. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
Abnormal specimens of Egirdira nigra (Kosswig & Geldiay, 1952) were gathered from Eğirdir Lake, Akkeçili Village, Türkiye, during standard ichthyological investigations in the area from May–September 2021. These specimens exhibited irregularities in the dorsal and pelvic fin. The abnormalities noted in these fins encompass the complete absence of the fin and various degrees of distortions in the fin’s components. The X-ray images revealed skeletal deformities are deliberated. Our findings underscored the necessity for enhanced monitoring of the freshwater environment and pinpointing the precise factor responsible for these irregularities.